Probiotic and postbiotic activity in health and disease: comparison on a novel polarised ex-vivo organ culture model. Issue 7 (1st February 2012) - Tsilingiri, Katerina; Barbosa, Theolis; Penna, Giuseppe; Caprioli, Flavio; Sonzogni, Angelica; Viale, Giuseppe; Rescigno, Maria
Abstract : Background and aims: Probiotics and their metabolic products, here called postbiotics, have been proposed as food supplements for a healthier intestinal homeostasis, but also as therapeutic aids in inflammatory bowel disease (IBD) with, however, very little clinical benefit. This may be due to the lack of reliable preclinical models for testing the efficacy of different strains. Methods: The activity of three probiotic strains of Lactobacillus (or a postbiotic) was analysed and compared with a pathogenic strain of Salmonella on a novel organ culture system of human healthy and IBD intestinal mucosa developed in our laboratory. The system maintains an apical to basolateral polarity during stimulation due to the presence of a glued cave cylinder. The cylinder is detached at the end of the experiment and the tissue is processed for histology and immunohistochemistry. Cytokines released from the basolateral side are analysed. Results: The model system provides several physiological characteristics typical of a mucosal microenvironment including the presence of an organised mucus layer and an apical to basolateral polarity. Polarised administration of bacteria is critical to control the ensuing immune response as it mimics the physiological entrance of bacteria. The authors show that probiotics are not always beneficial for the healthy host and can also be detrimental in inflamed IBD. This study shows that a potent postbiotic can protect against the inflammatory properties of invasive Salmonella on healthy tissue and also downregulate ongoing inflammatory processes in IBD tissue. Conclusions: Probiotics can have inflammatory activities in both healthy and IBD tissue. Valid preclinical data on proper model systems should therefore be obtained before specific probiotic strains enter the clinics, especially if administered during acute inflammatory responses. Postbiotics may be a safe alternative for the treatment of patients with IBD in the acute inflammatory phase.